Self-prescribed nutrition supplements for hair loss following laparoscopic sleeve gastrectomy bariatric surgery: extent of the problem in a cohort of Chinese patients (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Hair loss is common after bariatric surgery. This study analyzes the extent and risk factors of hair loss following laparoscopic sleeve gastrectomy (LSG), and satisfaction of self-prescribed supplements.Methods: All patients of LSG bariatric surgery during June 2013 to August 2016 at Shanghai East Hospital affiliated to Tongji University, Shanghai, China were included in the study. Study variables were- age, gender, preoperative body mass index, hemoglobin, albumin, total cholesterol, iron, zinc, copper, folic acid, vitamin B12, vitamin D, and postoperative excess weight loss (% EWL), time and degree of hair loss, satisfaction of using supplements. Logistic regression was used to analyze risk factors for hair loss.Results: Total of 86 patients underwent LSG. After exclusion data on 54 patients (M=11, F=43) were analyzed. Hair loss was reported by 42/54 (77.8%, M=6, F=36), starting at 3.43±1.36 months and ending at 8.59±3.38. All of 11 severe hair losses were in female. The female gender, preoperative serum folic acid, and %EWL were significant risk factors for hair loss. Hair regrowth was reported by 39/42 (92.86%). The 15 patients who used various self-prescribed iron and zinc supplements reported no satisfactory benefit.Conclusions: Hair loss was seen in 3/4th of patents after LSG bariatric surgery. Self-prescribed nutrition supplements were used by 1/3 of patients without satisfaction. Female gender, preoperative serum folic acid, and %EWL were significant risk factors for hair loss.